Trends of Creative Thinking Skill Research in Chemistry Education Journal Across Indonesia - Radjawaly Usman Rery; Tri Padila Rahmasari (STAI Hubbulwathan Duri, 2023)
This study focuses on analyzing how trend research about creative thinking ability in chemistry. This research contains an analysis study with the number of articles published in chemistry education with the research in Indonesia from 2018-2022. Studies are carried out on 23 journal articles, including from different journals with the scope in Indonesia search engine journal uses publish or perish with determined inclusive criteria. Publish or Perish is a software that retrieves and analyze academic citations and uses a variety data of sources. Step analysis started with reading the abstract and data reduction also data inference based on the research instrument used. Topic research involves publication number, types of research, chemistry material studied, research subject, and data analysis technique. The main research is quantitative research on hydrocarbon material with an analysist technique by using mean. Based on the result, some recommendations can be guidance for further study so that the research result is more useful and has an impact on Indonesian life especially in teaching and learning terms.